TREND RISET NEUROPEDAGOGI DAN IMPLEMENTASINYA DALAM PENDIDIKAN - Neneng Maryam Jamaliah Nurul Janah; Asep Supena (Universitas Pendidikan Indonesia, 2021)
This article aims to review the development of neuropedagogy research and its implementation in education. The method of writing this article is to use literature study (literature review). In this study twenty articles were chosen between the years 2016-2019 taken from google scholars' sources on the topic of neuropedagogy in education. Research on neuropedagogy has experienced significant developments, various scientific fields have sought to integrate neuropedagogy as an approach, technique and learning method to optimize student performance in learning. Various levels of education starting at the level of early childhood education until students have become the target of a neuropedagogical approach, but research on the implementation of neuropedagogy at the elementary school level has not been much researched. This is what underlies the authors to conduct a review of neuropedagogical research trends, so that it becomes a recommendation for further follow-up research, especially in the field of basic education.